Decreased Rate of Complications in Carpal Tunnel Release with Hand Fellowship Training - Mathen, Santosh J.; Nosrati, Naveed N.; Merrell, Gregory A. (Journal of Hand and Microsurgery, 2018)
Purpose In many procedures, both high case volumes and fellowship training have been shown to improve outcomes. One of the most common procedures performed by hand surgeons, the carpal tunnel release (CTR) is also performed by several other specialties without specialty training in a hand fellowship. This study analyzed the effect that hand fellowship training has on outcomes of CTRs.Materials and Methods Using the American Board of Orthopedic Surgeons (ABOS) Part II candidates’ case list submissions, a database was created for all open and endoscopic CTRs. Surgeon training, demographics, technique, and complications were recorded. Complications were then categorized and broken down by technique. Results were then analyzed for statistical significance.Results A total of 29,916 cases were identified. Hand fellowship–trained surgeons performed six times more CTRs at 31 cases per surgeon compared with five for non-hand fellowship–trained surgeons. They also improved outcomes in rates of infection, wound dehiscence, and overall complications. Rates of nerve injury or recurrence showed no statistical difference. This held true for the open release subset. Endoscopically, fellowship-trained surgeons had only improved rates of overall complications.Conclusion Surgeons undergoing additional hand fellowship training may show improved outcomes in the surgical treatment of carpal tunnel syndrome. However, no effect was seen on nerve injury or recurrence of symptoms.
Keywords: hand fellowship; carpal tunnel release; median nerve